Development of History of Bukxara Goldsmith’s Art - Jo’rayeva Madinaxon Anasbekovnaqizi; Xoliqov Kurbanali Madaminovich (Research Parks Publishing LLC, 2021)
This article describes the development of civilization in the world and the culture of the oven, the center of the religion of islam says the city of Bukhara Sharif, recognised the practical analysis of the historical development of the The Curse of Zarda'z will be covered.